An assessment of the emergency response among health workers involved in the 2010 cholera outbreak in northern Nigeria - David A. Oladele; Kolawole S. Oyedeji; Mary-Theresa Niemogha; Francisca Nwaokorie; Moses Bamidele; Adesola Z. Musa; Adeniyi K. Adeneye; Tajudeen A. Bamidele; Michael Ochoga; Kehinde A. Akinsinde; Bartholomew I. Brai; Emmanuel A. Omonigbehin; et al. (Elsevier, 2012)
Summary: Background: The 2010 cholera outbreak in northern Nigeria affected over 40,000 people, with a case fatality rate (CFR) of ≥3.75%. We assessed the emergency response of health care workers (HCWs) involved in case management. Method: This was a cross-sectional study with data collected through a self-administered questionnaire. Data entry and analysis were performed using Epi info software. Results: A total of 56 HCWs were interviewed. The mean age was 31 years (SD ± 8.16 years). The majority of the HCWs (80%; n = 45) were aged 18-39 years. Most were community health extension workers (60%), and 3.6% (n = 2) were medical doctors. Many of the HCWs had less than 2 years of work experience (42%). Additionally, 82% of the respondents had <1 week of cholera emergency response training, and 50% of the HCWs managed >20 suspected cases of cholera per day. Although 78% of HCWs reported the practice of universal safety precautions, 32% (n = 18) knew HCWs who developed symptoms of cholera during the epidemic, most of which was believed to be hospital acquired (78%). We also found that 77% (n = 43) of HCWs had no access to the required emergency response supplies. Conclusion: Inadequate training, a lack of qualified HCWs and a limited supply of emergency response kits were reported. Therefore, the government and stakeholders should address the gaps noted to adequately control and prevent future epidemics. Keywords: Cholera, Emergency response, Healthcare workers, Nigeria